2013
DOI: 10.1002/srin.201300061
|View full text |Cite
|
Sign up to set email alerts
|

New Evaluation Methods Discussion of Softening–Melting and Dropping Characteristic of BF Iron Bearing Burden

Abstract: Based on the analysis of the existing evaluation methods and with the combination of the characteristic of cohesive zone characteristic in blast furnace (BF) and softening–melting and dropping experimental result of iron bearing burden, a new evaluation method of softening–melting and dropping characteristic of iron bearing burden was put forward, which can be used for evaluating various kinds of iron bearing burden. The softening–melting and dropping characteristics of the mixed burden and the high metalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…For operational purposes, it is preferred to have a deep or low cohesive zone in the BF. It helps in preventing the gas flow close to the wall, which in turn minimizes the coke rate . This can be achieved by having a minimum temperature difference between the softening and melting of ferrous materials.…”
Section: Introductionmentioning
confidence: 99%
“…For operational purposes, it is preferred to have a deep or low cohesive zone in the BF. It helps in preventing the gas flow close to the wall, which in turn minimizes the coke rate . This can be achieved by having a minimum temperature difference between the softening and melting of ferrous materials.…”
Section: Introductionmentioning
confidence: 99%
“…1-4 of Table 3 are shown in Figure 4 As can be seen from the ternary phase diagram of FeO-SiO 2 -CaO(Figure 5), FeO and SiO 2 can well reduce the melting point of slag and form low melting point materials, such as 2FeO•SiO 2 (melting point 1217°C) and CaO x (FeO) 1.81 SiO 2 (melting point 1150 °C) [18]. Ferrous oxide affects the formation of primary slag to a great extent [19]. With the increase in hydrogen content in reduction gas, the reduction rate of iron ore increases, and the content of FeO is reduced, so that the formation temperature of primary slag increases and the formation slag amount decreases, which leads to the increase in initial softening temperature T 10 of furnace charge.…”
Section: Effect Of Hydrogen Content On Softening and Melting Performa...mentioning
confidence: 99%
“…Coke-ore mixed charging improved the softening-dripping properties of packed bed, but the fluidity of slag and dropping behavior was bad when coke-ore mixing ratio was increased to 50% [15]. In order to better understand the softening-melting characteristic of iron-bearing burden, Wu et al investigated a new method for evaluating softening-melting behavior, and found that unit charge column maximum pressure drop, pressure drop range, and unit charge column pressure drop can better reflect the permeability and liquid fluidity of burden [16]. The composition of burden has an important effect on the softening and melting properties.…”
Section: Introductionmentioning
confidence: 99%